Past human‐induced ecological legacies as a driver of modern Amazonian resilience - Crystal N. H. McMichael; Mark B. Bush; Juan C. Jiménez; William D. Gosling (People and Nature, 2023)
Abstract People have modified landscapes throughout the Holocene (the last c. 11,700 years) by modifying soils, burning forests, cultivating and domesticating plants, and directly and indirectly enriched and depleted plant abundances. These activities also took place in Amazonia, which is the largest contiguous piece of rainforest in the world, and for many decades was considered to have very little human impact until the modern era. The compositional shift caused by past human disturbances can alter forest traits, creating ecological legacies that may persist through time. As the lifespan of most Amazonian tree species is more than 200 years, forests that were modified over the last centuries to millennia are likely still in a mid‐successional state. Ecological legacies resulting from past human activity may also affect modern forest resilience to ongoing anthropogenic and climatic changes. Current estimates of resilience assume that forests are in equilibrium, and long‐term successional trajectories are not considered. We suggest that disturbance histories, generated through palaeoecological and archaeological surveys, should be paired with field‐based and remotely sensed estimates of forest resilience to recent drought events, to determine whether past human activities affect modern forest resilience. We have outlined how this can be accomplished in future research. Read the free Plain Language Summary for this article on the Journal blog.